A Contrastive Analysis of Fi’il Mudhari’ and Its English Translation Equivalents in Surah Al-Kahf: A Study of Saheeh International Translation - Melgiyani; Dedi Sulaeman; Andang Saehu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study analyzes the functions of fi’il mudhari’ in Surah Al-Kahf and their English translation equivalents in the Saheeh International translation. Although previous studies have discussed fi’il mudhari’ and the relationship between Arabic and English tenses, few studies have focused on how the various meanings of fi’il mudhari’ are translated into English in Qur’anic texts. Therefore, this study aims to identify the functions of fi’il mudhari’ in Surah Al-Kahf and explain how these functions are represented in English translation. This study uses a qualitative descriptive method with a contrastive analysis approach to compare Arabic and English grammatical and semantic systems. The data consist of 162 occurrences of fi’il mudhari’ found in Surah Al-Kahf (verses 1–110). The findings show that fi’il mudhari’ has wider meanings and functions than the English simple present tense. In many cases, it is translated into the simple present when expressing habitual actions, repeated activities, and general truths. However, fi’il mudhari’ can also express future meaning, purpose, commands, prohibitions, and other meanings depending on the context and grammatical structure. As a result, its English translations appear in different forms, such as the simple present, future, modal, infinitive, and imperative forms. The study also finds that English simple present forms do not always come from fi’il mudhari’. Some are translated from other Arabic structures, including jumlah ismiyyah, ism fa’il, and ism tafdil. These findings help explain the differences between Arabic and English grammatical systems and provide a better understanding of Qur’anic translation. The study concludes that the relationship between fi’il mudhari’ and the English simple present tense is only partial because the meaning of fi’il mudhari’ depends not only on grammar but also on context.